2015
DOI: 10.4103/1735-9066.161002
|View full text |Cite
|
Sign up to set email alerts
|

Challenges associated with the implementation of the nursing process: A systematic review

Abstract: Background:Nursing process is a scientific approach in the provision of qualified nursing cares. However, in practice, the implementation of this process is faced with numerous challenges. With the knowledge of the challenges associated with the implementation of the nursing process, the nursing processes can be developed appropriately. Due to the lack of comprehensive information on this subject, the current study was carried out to assess the key challenges associated with the implementation of the nursing p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 50 publications
(24 citation statements)
references
References 78 publications
0
24
0
Order By: Relevance
“…The acronym "VIPS" reflects the Swedish words for Wellbeing, Integrity, Prevention and Safety. The VIPS model provides a structure for nursing documentation based on the "Nursing Process" (Ehrenberg et al, 1996;Zamanzadeh, Valizadeh, Tabrizi, Behshid, & Lotfi, 2015).…”
Section: Author Manuscriptmentioning
confidence: 99%
“…The acronym "VIPS" reflects the Swedish words for Wellbeing, Integrity, Prevention and Safety. The VIPS model provides a structure for nursing documentation based on the "Nursing Process" (Ehrenberg et al, 1996;Zamanzadeh, Valizadeh, Tabrizi, Behshid, & Lotfi, 2015).…”
Section: Author Manuscriptmentioning
confidence: 99%
“…The nursing process is a scientific approach to providing high quality nursing care. [ 50 ] Nursing process standardizes and improves nursing care. Previous studies have indicated that the quality of nursing cares and their effects will be increased because of nursing care on the basis of the nursing process.…”
Section: Discussionmentioning
confidence: 99%
“…Intangible understanding of the meaning of nursing process, difference in attitudes toward the nursing process, lack of awareness of the nurses, and supportive management of problems related to recording the nursing process were the main challenges in reviewed literatures. [32] Apesoa-Varano believes that while nursing student's think of the occupation as a profession, their understanding of what makes a “good” nurse is deemphasized in the model of professionalism espoused by their educational program. Consequently, prospective nurses must reconcile their expectations of nursing as a caring occupation with the professional ideology of the program.…”
Section: Discussionmentioning
confidence: 99%